Treatment of Elbow Osteomyelitis With an Interposition Arthroplasty Using a Rectus Abdominis Free Flap. (May 2015) - Jaiswal, Rohit; Busse, Brittany; Allen, Robert; Sahar, David
Abstract : Introduction: Osteomyelitis of the elbow may be a complex clinical problem. Treatment goals include the eradication of infection and preservation of maximal joint function. Bony debridement may be necessary in addition to elbow joint arthroplasty. The use of synthetic material or allograft as the arthroplasty material may be contraindicated in the setting of infection. The use of free muscle transfer as an arthroplasty medium has not been well described. Methods: A 22-year-old paraplegic man developed recurrent osteomyelitis of the right elbow, necessitating extensive bony debridement by the orthopedic surgery team. Reconstruction arthroplasty was performed using a free rectus abdominis muscle flap as the arthroplasty material to serve as a source of biologically active, well-vascularized arthroplasty medium in the presence of ongoing infection. Results: A successful free muscle flap arthroplasty was performed. External fixation and physical therapy were implemented postoperatively. The patient had resolution of osteomyelitis and excellent functional use of the elbow for activities of daily living and wheelchair motion. Conclusions: Elbow arthroplasty in the setting of active infection may be accomplished by means of free tissue muscle transfer. Elimination of infection and acceptable joint function may be possible with this form of reconstruction. Abstract : Supplemental digital content is available in the text.